Formulation of Resveratrol Nanoemulsion by Phase Inversion Technique and Evaluation of Anti-Cancer Activity on Human Colon Cancer Cell Lines - Kotta, Sabna (Indian Journal of Pharmaceutical Education and Research, 2021)
Colorectal cancer is in third place among the most usually detected cancer worldwide. Many natural compounds have been proved for its efficacy in the treatment of different types of carcinomas. Resveratrol a polyphenolic phytoalexin found in several sources including grapes, berries, etc. Like most of the polyphenols resveratrol also exhibits poor aqueous solubility and hence bioavailability. In this study nanoemulsion of resveratrol has been formulated using a low energy technique (phase inversion composition) using capryol as oil phase. The optimized formulations were evaluated for size of nanodroplets, zeta potential as well as in vitro drug release. The resveratrol nanoemulsion was evaluated on HCT-166 cell lines to study the inhibitory effect on the viability of human colorectal cancer cell and compared with resveratrol suspension and blank nanoemulsions. Transmission electron microscopy and dynamic light scattering revealed the globule size of nanoemulsion was 113.6 ±18.21 nm with a zetapotential of -15.12±1.028. In vitro release profile showed above 80% release within 6 hr. The results of the cell line studies showed that the developed resveratrol nanoemulsion was cytotoxic to the colon cancer cells while non-toxic to the non-tumor cells. Hence, the developed resveratrol nanoemulsion was proved to be a promising approach for colon cancer management.
Keywords: Resveratrol; Lung cancer; HCT-166 cells; Nanoemulsion; Phytochemicals